Gloss on the Supreme Court ruling of 24 January 2018, II KK 10/18 (Ius Novum, 2019)
The author of the gloss approves of the thesis expressed in the Supreme Court ruling of 24 January 2018, II KK 10/18, in accordance with which the framework of the jurisdictional proceedings are determined by a historical event described in the indictment and not by particular elements of this description. The time of an act commission is one of the elements of the subjective aspect of an offence. It is subject to determination by a court and may be specified in a different way from that in the description of an act alleged in the indictment, provided that the evidence taken at a trial justifies such a change. The sole finding that the event covered by the indictment took place at the time different from that specified in it is admissible and does not mean going beyond the limits of a prosecutor’s complaint. Having analysed the Supreme Court and appellate courts’ adjudication practice, the author highlights additional elements of an act description that do not lead to going beyond the limits of an indictment. The gloss also covers the issue of the obligation to inform the parties present at a trial about the possibility of changing the legal classification of an act (Article 399 CPC) and the so-called incidental proceedings in the context of the identity of the act alleged in the indictment and the one attributed in the sentence.
Keywords: limits of the indictment; identity of an act alleged in the indictment and attributed in the sentence; change in the legal classification of an act; incidental proceedings; principle of accusatorial system; immutability of the subject matter of a trial